Development of a finite element matrix (fem)three-phase three-limb transformer model for Geomagnetically Induced Currents (GIC) experiments - Mkhonta, Sizwe (Department of Electrical Engineering, 2021)
Geomagnetically Induced Currents (GIC) have been a growing concern within power system operators and researchers as they have been widely reported to lead to power system related issues and material damage to system components like power transformers. In power transformers, GIC impacts are evidenced by part-wave saturation, resulting in transformers experiencing increased presence of odd and even harmonics. The three-phase three-limb (3p3L) transformer has been found to be the most tolerant to high dc values compared to other core types. The research was based on a hypothesis which reads “transformer laboratory testing results can be used as a guide towards developing suitable Finite Element Matrix (FEM) models to be used for conducting GIC/DC experiments”. This study thus investigates the response of a 15 kVA 3p3L laboratory transformer to dc current, emulating the effects of GICs. GIC and dc current are the same under steady state conditions, and hence mentioned interchangeably. Laboratory tests conducted identified two critical saturation points when the transformer is exposed to dc. The early saturation point was identified to be at around 1.8 A/phase of dc (18% of rated current), while the deep saturation point was at around 15 to 20 A/phase of dc (about 72% of rated current). Further analysis showed that holes drilled on the transformer can lower the transformer knee-point by about 26%, depending on the size and location of the holes. The holes hence end up affecting the operating point of the transformer due to losses occurring around the holes. A transformer FEM model was developed following the laboratory exercise, where it was concluded that a 2D model leads to grossly erroneous results, distorting the magnetizing current by about 60% compared to the laboratory results. A solid 3D model improved performance by about 30% as it took the transformer's topological structure into consideration. The 3D model was then refined further to include joints and laminations. It was discovered that laminations on the transformer need to be introduced as stacks of the core, with each core step split into two, allocating a 4% air gap space between stacks. Refinement of the T-joints proved that the joints have a relatively high influence on the transformer behaviour, with their detailed refinement improving the transformer behaviour by about 60%. The final FEM model was used for dc experiments. The results of such experiments showed close resemblance to the laboratory results, with saturation points identified in FEM lying within 10% of the laboratory identified saturation points. Overall, the various investigation methods explored showed that the hypothesis was satisfactorily proven true. Laboratory results functioned as a guide in developing the model, offering a reference case.